THE EFFECT OF SCORE STRATEGY AND READING MOTIVATION TOWARD STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXTS AT GRADE X SMA NEGERI 2 PADANG - Satria, Willy (Jurnal Curricula, 2016)
This research was quasi experimental research with factorial 2x2 design. Population of the research was grade X students with the total population was 224. The sample was taken by using cluster random sampling, class MIA 2 as experimental group and class MIA 3 as the control group. To collect the data, the researcher used reading comprehension test while questionnaire was used to collect the data about students’ reading motivation. Then, the collected data were analyzed by Chi-Square for normality data testing, variance test for homogeneity data testing, t-test formula and ANOVA for hypothesis testing.            The analysis of the research reveals that: (1) students who are taught by SCORE strategy get better reading comprehension on narrative text  than the students who are taught by Guided Reading strategy, (2) the students with high reading motivation who are taught by SCORE strategy do not get better reading comprehension on narrative text than who are taught by using Guided Reading strategy, (3) the students with low reading motivation who are taught by SCORE strategy get better reading comprehension on narrative text than who are taught by using Guided Reading strategy, (4) there is no interaction between both strategies and students’ reading motivation toward their reading comprehension on narrative text. In conclusion, SCORE strategy is an effective way on students’ reading comprehension compared with Guided Reading. It is suggested for the students that have high and low reading motivation to improve their skill in language learning through SCORE strategy.